Hubungan Sensory Processing Knowledge dan Parental Self-Efficacy pada Ibu dengan Anak Penyandang Autism Spectrum Disorder - Dion Pratama; Agustina Hendriati (Humanitas (Jurnal Psikologi), 2021)
Autism Spectrum Disorder (ASD) cases keep increasing in Indonesia, hence the increasing need of adequate capabilities in mothers with ASD child. However, raising an ASD child is not easy and mothers may lose their Parental Self-Efficacy during the process. To improve Parental Self-Efficacy, mothers need relevant strategies such as Sensory Processing Knowledge. Research in the United States has proven the positive influence of Sensory Processing Knowledge on Parental Self-efficacy. However, it is necessary to confirm such result in the context of Indonesian collective culture. This study involved 50 mothers with ASD child. The research instruments were KEPSA and PASEC. Spearman Rank-Order Correlation Test showed that Sensory Processing Knowledge did not have a significant positive relationship with Parental Self-Efficacy of mothers with ASD child in Indonesian context. The discussion shed further need to understand how characteristics of mothers in collectivistic cultures may be involved in the way they raise an ASD child. Further research were suggested to examine the contribution of various factors that may affect Parental Self-Efficacy. Keywords: parental self-efficacy, sensory processing knowledge, autism spectrum disorder, collective culture